The Investigation of Biofeedback and Neurofeedback Training on Athletic Performance-systematic Review - Bence F. Nagy; József Márton Pucsok; László Balogh (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The investigation of biofeedback and neurofeedback training on athletic performance-systematic review. The present study aimed to systematically review the impact of biofeedback and neurofeedback training on sports performance. We investigated both theoretical and practical aspects of biofeedback and neurofeedback techniques. The screened articles involved athletes from various individual and team sports. Participants of the reviewed studies had different levels of experience, from novice to professional. We examined multiple devices and instrumentation (EEG, EMG, Nexus 10, telemetry, etc.) that may facilitate athletes' mental preparation. We also provided an overview of the protocols used with different monitoring devices. This study reviewed current biofeedback and neurofeedback techniques for preparing competitive athletes. Research has shown that athletes using the biofeedback method in their training routines are far more effective in terms of mental preparation than control groups. The researchers also found that the techniques used by athletes needed to be developed and adapted to more sports. This review identified different groups that could benefit from biofeedback-based interventions in sports. Interventions have generally had a positive effect on coping with anxiety.